O uso do vídeo na Sala de Aula Invertida: uma experiência no Colégio Arbos de Santo André - Molina, Verónica Andrea Peralta Meléndez (2017)
This project reflects about the use of educational videos as a learning tool in Flipped Classroom and discusses what applications and strategies can be used with this new methodology for better use, both the student and the teacher. In our analysis, the use of this methodology allows construction of a significant learning with more dynamism and autonomy, improving the use of the proposed activities and topics in the classroom. In this research, we will also point out how using video in Flipped Classroom makes classes with less extensive explanations possible, direct and objective, when recorded on video that can be accessed by students through mobile devices, desktop computers and Ipads. Class time is released for use in other learning activities such as individual exercises or in pairs, discussion, projects or group work, having the teacher available in the classroom to act as mediator. The research noted the use of the videos in Flipped Classrooms in ‘Colégio Arbos’, in Santo André, and tried to understand if this tool helped in building meaningful learning and how it helped. The research methodology that was used was the case study. The teachers answered a questionnaire and the dice studies were performed through content analysis of Bardin